Integrating remote datasets to identify precontact architecture and settlement patterns along the Wampu River system, Eastern Honduras - Cohen, Anna S.; Fernandez-Diaz, Juan Carlos; Groat, Elizabeth; Eury, Quinn (PLOS ONE, 2025)
In our era of remote sensing archaeology and legacy datasets, multiple lines of evidence should be integrated to establish a large-scale view of threatened Indigenous landscapes. This study brings together several datasets derived from airborne lidar, satellite imagery, and pedestrian survey to present the first large-scale (>650 km2) synthesis of the settlement archaeology of the Wampu River system, a part of eastern Honduras with limited archaeological work. The purpose of this study is to: 1) connect pedestrian and airborne lidar surveys within the Wampu River system; 2) identify patterns in archaeological sites and architecture; 3) characterize the anthropogenic landscape of the region, and to suggest areas for future work in this understudied part of the Americas. Results include the identification of 72 archaeological sites, 55 of which were previously unreported, and the creation of a basic classificatory scheme for site organization. Other findings include the preliminary observations that water, topography, and seasonality likely structured settlement patterns, and that there are emerging patterns in site orientation. We also consider how eastern Honduras could contribute to broader discussions about tropical settlement patterns. Overall, this study demonstrates that eastern Honduras has the potential for future research identifying extensive settlements in the centuries before European arrival, thus contributing to a more complex understanding of the extent and diversity of Indigenous populations in the Americas.